Invigorasi Benih Mentimun (Cucumis sativus L.) Kadaluarsa melalui Teknik Hydropriming Air Kelapa Muda dengan Lama Perendaman yang Berbeda - Iskandar, Hervyaningsih; Amalia, Lia; Rakhmi Indriana, Kovertina (OrchidAgro, 2025)
This research aims to study and determine the appropriate concentration and duration of soaking young coconut water to enhance the viability and vigor of expired cucumber seeds. The research were conducted in Panyingkiran Village, Purwadadi District, Subang Regency. The research will be conducted in August 2024. The experimental design used is a Randomized Block Design (RBD), with the treatments being: A = 0% young coconut water + 0 hours of soaking, B = 0% young coconut water + 10 hours of soaking, C = 0% young coconut water + 20 hours of soaking, D = 0% young coconut water + 30 hours of soaking, E = 25% young coconut water + 0 hours of soaking, F = 25% young coconut water + 10 hours of soaking, G = 25% young coconut water + 20 hours of soaking, H = 25% young coconut water + 30 hours of soaking, I = 50% young coconut water + 0 hours of soaking, J = 50% young coconut water + 10 hours of soaking, K = 50% young coconut water + 20 hours of soaking, L = 50% young coconut water + 30 hours of soaking, M = 75% young coconut water + 0 hours of soaking, N = 75% young coconut water + 10 hours of soaking, O = 75% young coconut water + 20 hours of soaking, and P = 75% young coconut water + 30 hours of soaking. The research results indicate that there is an effect of the concentration of young coconut water and the duration of soaking on the increase in viability and vigor of expired cucumber seeds. Treatment K gave the highest average value for the parameters of germination power, seed growth rate, wet weight of the sprouts, dry weight of the sprouts, and root shoot ratio in cocopeat seedling media. Meanwhile, treatment N provided the highest average values for the parameters of germination power, vigor index, seed growth rate, wet weight of the seedlings, dry weight of the seedlings, and root-to-shoot ratio in the sand seedling medium. Keywords: young coconut water; expired seeds; invigorate.